Psychosocial working conditions in today’s workplaces: towards an increased specificity in risk assessment and management / Attualità dei contesti lavorativi: verso una maggior specificità nella valutazione e gestione del rischio psicosociale - Conway, Paul Maurice; Camerino, Donatella (La Medicina del Lavoro, 2014)
New trends of the contemporary world of work, including the increasing globalization and flexibilization of the labour market, the occurrence of significant demographic shifts in the workforce as well as the predominance of the service sector, have profoundly affected the way work is today organized and managed. Parallel to these transformations, new risks and challenges have emerged in the field of occupational health and safety....